Diabetes at the Crossroads: Insulin Action and Insulin Resistance - Vinall, Maria (MD Conference Express, 2014)
Today, the study of diabetes is at the crossroads of insulin signaling and insulin resistance as the scientific community seeks to better understand insulin action, sites of regulation, and unoccupied receptor signaling. This article discusses some of the most recent research regarding insulin action and insulin resistance.